Biomedical simulation of non-newtonian fluid dynamics in cardiovascular systems: A finite volume method approach to pulsatile flow and atherosclerosis analysis - Tulus, Tulus; Mohammad Rasidi, Rasani; Rahman, Md Mustafizur; Suriati, ,; Marpaung, Tulus Joseph; Siringoringo, Yan Batara Putra; Marpaung, Jonathan Liviera (International Information and Engineering Technology Association, 2024)
The study of non-Newtonian fluid dynamics within cardiovascular systems is critical for understanding the complex interactions between blood flow and arterial health. This research focuses on the application of the Finite Volume Method (FVM) to simulate non- Newtonian fluid behavior under pulsatile flow conditions, mimicking the heartbeat. The objective is to analyze the effects of varying viscosity properties and flow patterns on the development and progression of atherosclerosis. By employing computational simulations, we investigate the rheological properties of blood, characterized as a non-Newtonian fluid, and its impact on shear stress distribution and arterial wall interaction. The simulation framework incorporates advanced non-Newtonian models, including Power-law and Carreau-Yasuda models, to accurately represent blood viscosity variations. Pulsatile flow dynamics are modeled to replicate physiological conditions, providing insights into the mechanical forces exerted on arterial walls and their role in atherosclerotic plaque formation. The results highlight critical areas of high shear stress and low shear rate, which correlate with regions prone to atherosclerosis. This study's findings contribute to a deeper understanding of cardiovascular fluid mechanics and offer potential implications for medical diagnostics and treatment strategies for atherosclerosis. The application of the FVM in this context demonstrates its robustness in handling complex fluid behaviors and geometries, paving the way for more sophisticated simulations in biomedical engineering.